Self-protective Oxide Nano-Coatings for Enhanced Surface Biocompatibility of Titanium. Issue 1806 (2015) - Ozdemir, Zeynep; Craciun, Valentin; Basim, Bahar
ABSTRACT: The biocompatibility of an implant material depends on the bulk physical properties in addition to the surface properties. In biomedical engineering and industry Ti and Ti-alloys are very popular biological implant material for their bulk physical properties and strength to weight ratio resembling those of nature bone. It is possible to modify the surface properties of titanium for enhanced surface biocompatibility. The main objective of the this study is to engineer a smart Ti-based prosthesis surface by self induced chemically modified titanium oxide nano-film by the chemical mechanical polishing process (CMP). This new process applied on bio-implants aims at significantly reducing the out-diffusion of Ti and other metallic impurities from prosthesis in contact with body fluids and tissue and simultaneously enhancing the surface mechanical, chemical and biological properties. CMP technique enables the growth of a thicker and denser self-protective native oxide on Ti and Ti alloy samples, while simultaneously inducing a controlled surface roughness. It is demonstrated that the Ti based dental implants with self-protective oxide induced surfaces help minimize chemical and bacterial reactivity in addition to Ti ion dissolution while promoting their biocompatibility through surface patterning. The studied self-protective oxide films can also be utilized for many additional applications including bio-sensors.